HOLTON, KAN. REV. ORDINANCES No. 169, § 21 at 130, 134-35 (1905) (effective Aug. 8, 1888). - (:unkn) unknown (General Publisher, 1888)
Any minor who shall have in his possession any pistol, revolver or toy pistol by which cartridges may be exploded, or any dirk, bowie knife, brass knuckles, slung shot or any other deadly weapons, shall, upon conviction thereof, be fined not less than one or more than ten dollars."
--
Keywords: TRANSFER - MINORS